Omics : applications in biomedical, agricultural, and environmental sciences - Barh, Debmalya.; Zambare, Vasudeo.; Azevedo, Vasco. (CRC Press/Taylor & Francis, 2013)
"With contributions from active researchers, this book explores emerging fields such as metagenomics, cytomics, glycomics, miRNA and their various applications, demonstrating the real diversity of omics. It covers cutting edge treatments such as toxicognenomics and its applications in assessment of environmental pollutants, applications of plant metabolomics, nutrigenomics and its therapeutic application, microalgal Omics and their applications in bio-fuel development. Next generation sequencing and Omics technology for transgenic plant analysis is also included"--Provided by publisher.